2011
DOI: 10.1172/jci57673
|View full text |Cite|
|
Sign up to set email alerts
|

Integrin α6β4 identifies an adult distal lung epithelial population with regenerative potential in mice

Abstract: Laminins and their integrin receptors are implicated in epithelial cell differentiation and progenitor cell maintenance. We report here that a previously unrecognized subpopulation of mouse alveolar epithelial cells (AECs) expressing the laminin receptor α6β4, but little or no pro-surfactant C (pro-SPC), is endowed with regenerative potential. Ex vivo, this subpopulation expanded clonally as progenitors but also differentiated toward mature cell types. Integrin β4 itself was not required for AEC proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
257
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(277 citation statements)
references
References 27 publications
(30 reference statements)
11
257
1
1
Order By: Relevance
“…However, a new study showed that cells labeled with the Scgb1a1CREER contribute extensively to the alveoli regener ation after bleomycininduced lung injury, suggesting that the contribution of Clara cells to lung regeneration can vary depend ing on the type of injury . Consistent with the role of Scgb1a1+ cells during lung repair after bleomycin induced injury, lineage tracing of alveolar type 2 cells using SPCCREER demonstrated that SPCderived cells are re placed by SPCnegative progenitors during lung repair after bleomycin inhalation (Chapman et al, 2011). K14CREER lin eage tracing suggested that K14/K5positive cells appear in the bronchioles a few days postinfection of H1N1 virus and give rise to migrating K5positive clusters of cells at the sites of interbronchiolar lung damage (Kumar et al, 2011).…”
Section: The Airway Systemmentioning
confidence: 73%
“…However, a new study showed that cells labeled with the Scgb1a1CREER contribute extensively to the alveoli regener ation after bleomycininduced lung injury, suggesting that the contribution of Clara cells to lung regeneration can vary depend ing on the type of injury . Consistent with the role of Scgb1a1+ cells during lung repair after bleomycin induced injury, lineage tracing of alveolar type 2 cells using SPCCREER demonstrated that SPCderived cells are re placed by SPCnegative progenitors during lung repair after bleomycin inhalation (Chapman et al, 2011). K14CREER lin eage tracing suggested that K14/K5positive cells appear in the bronchioles a few days postinfection of H1N1 virus and give rise to migrating K5positive clusters of cells at the sites of interbronchiolar lung damage (Kumar et al, 2011).…”
Section: The Airway Systemmentioning
confidence: 73%
“…In the alveolar space, where gas exchange is carried out by alveolar epithelial type 1 (AT1) cells, the surfactant-expressing AT2 cells can function as stem cells 60,142 . Another alveolar cell population, expressing α6β4 integrin, can also produce alveolar epithelia 142,143 . Bronchioalveolar stem cells (BASCs), which reside between the airway and alveolar space, can give rise to both epithelial lineages 56,114,144146 .…”
Section: Figurementioning
confidence: 99%
“…To determine which of the mesenchymal lineages identified preferentially promote alveolar cell growth and self-renewal, alveolar organoid assays were performed using mature AT2 cells isolated from Sftpc CreERT2 : R26R EYFP adult mice (Barkauskas et al, 2013; Chapman et al, 2011). The five different mesenchymal lineages or populations were combined with AT2 cells to form organoids and were subsequently counted, sectioned for IHC, and isolated for gene expression analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%